Joint Planning of Regional Integrated Energy System Based on Enhanced Benders Decomposition - LIU Bingwen, WU Xiong, CAO Binrui, MA Song, HE Wenwen (Shanghai Jiaotong Daxue xuebao, 2024)
With the gradual marketization of energy trading, different economic entities such as the integrated energy service provider (IESP) and user aggregators (UAs) will form within the regional integrated energy system (RIES). The coordination of all entities to participate in joint planning for a globally optimal planning scheme while protecting privacy has posed a new challenge for RIES planning. First, the structure of the coupled electrical-gas-thermal RIES is clarified in this paper, and a mathematical model is constructed from IESP, UA, and electrical-gas-thermal network. Then, a RIES joint planning model considering IESP and multiple UAs is proposed with the objective of economical optimization. Afterwards, in order to adapt to the non-convexity of the sub-problem of the joint planning problem, the enhanced Benders algorithm is proposed to realize the distributed solution of the model, which protects the privacy of all entities to the greatest extent. Finally, the advantages of the joint planning scheme in terms of economy and energy efficiency are analyzed by comparing four sets of cases, and the good convergence of the proposed distributed algorithm is verified.